Has There Been a She-covery? The Financial Crisis of 2008 and Its Impact on the Ontario Labour Market - Lewchuk, Wayne (Relations industrielles / Industrial Relations, 2013)
This paper explores changes in labour market outcomes between June 2005 and November 2010. It asks if the recovery in labour markets following the 2008 financial crisis favoured men or women. The analysis is based on a unique longitudinal database of individuals in the Toronto-Hamilton labour market. Men were the most likely to have paid employment in the post-financial crisis period, but only at the cost of a significant deterioration in its terms and conditions. The findings suggest that many middle-aged workers were not protected by job seniority or implicit lifetime employment relationships. The findings point to a further decline in the prevalence of the standard employment relationship and the male breadwinner model of employment.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Economic recovery; Employment; LABOR market; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies